Evaluation of color removal and degradation of a reactive textile azo dye on nanoporous TiO2 thin-film electrodes - Carneiro, P. A.; Osugi, M. E.; Sene, J. J.; Anderson, M. A.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2004)
The feasibility of the photobleaching of a textile azo dye, reactive orange 16 (C.I. 17757), in aqueous solution using titanium dioxide thin-film electrodes prepared by the sol-gel method was investigated. The best conditions for maximum photoelectrocatalytic degradation were found to be pH > 10 for Na2SO4 medium and pH < 6 for NaCl. In both situations, an applied potential of +1.0 V and low dye concentration are recommended, when 100% of color removal is obtained after 20 min of photoelectrocatalysis. The effects of side reaction pathway on the degradation rate of dye in sulfate and chloride medium were presented and the best performance are optimized to situations closed to that verified in the textile effluent. The influence of variables as applied potential, pH, supporting electrolyte and dye concentration on the kinetics of photoelectrochemical degradation also were investigated. Oxalic acid is identified by HPLC and UV-Vis spectrophotometric methods as the main degradation product generated after 180 min of photoelectrocatalysis of 4 x 10(-5) mol l(-1) dye in sodium sulphate pH 12 and NaCl pH 4.0 and a maximum reduction of 56 and 62% TOC was obtained, respectively. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: TiO2 thin-film electrode; degradation of reactive dye; photoelectrocatalysis; dye oxidation; reactive orange 16